Are We There Yet? - Santat, Dan (New York ; Little, Brown and Company, 2016)
"A boy goes on a long car ride to visit his grandmother and discovers time moves faster or slower depending on how bored he is"--
Keywords: Space and time -- Fiction; Automobile driving -- Fiction